The intensity control improvement of the difficulty element training with ring in "Ormani Arenado" initial sport school 13 - 15 years old gymnasts of Gymnastic Rhythmic - Yolainy Govea-Díaz; Marlen Echevarría-Pérez; Irma Ismary LLanes-Galdo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
The constant changes of the demands in the Code of Punctuation of the last three Olympic cycles, demand more than ever today of an appropriate planning and control of the process of the gymnasts' sport preparation. The ways in which the intensity control of the difficulty elements training that will form the competitive exercises of the 13 - 15 years old gymnasts from Pinar del Río have been carrying out are not enough that is why it is necessary to improve it in agreement to the current characteristic of the sport starting from the previously outlined, a contradiction appears in the process of the Rhythmic gymnast's training, between the high levels of technical demands of difficulty elements execution and the absence of methodological tools to establish the requirements that as for training intensity allow to satisfy the same ones. This contradiction appears to be the issue of this problem. It is defined as the scientific problem: how to contribute to the intensity control improvement of the difficulty elements training of difficulty with the ring in "Ormani Arenado" Initial Sports School 13 - 15 years old gymnasts of Gymnastics Rhythmic? To solve this problem, it was traced as objective of this work: to elaborate a methodology for the intensity control of the training of the difficulty elements training with ring in individual gymnasts of Gymnastic Rhythmic category 13-15 years old of the EIDE Ormani Arenado. The tasks of the investigation were developed using statistical, theoretical, empiric and mathematical methods that are explained in the chapter II of the thesis. The novelty of this investigation is manifested in the methodology which is suggested as a new form of controlling the intensity of the elements training difficulty, starting from the selection of specific indicators of the activity that is carried out.